Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1074/jbc.m205164200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Calcium/Calmodulin-dependent Protein Kinase II Docking toN-Methyl-d-aspartate Receptors by Calcium/Calmodulin and α-Actinin

Abstract: Ca2؉ influx through the N-methyl-D-aspartate (NMDA)-type glutamate receptor leads to activation and postsynaptic accumulation of Ca 2؉ /calmodulin-dependent protein kinase II (CaMKII) and ultimately to long term potentiation, which is thought to be the physiological correlate of learning and memory. The NMDA receptor also serves as a CaMKII docking site in dendritic spines with high affinity binding sites located on its NR1 and NR2B subunits. We demonstrate that high affinity binding of CaMKII to NR1 requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
169
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(176 citation statements)
references
References 42 publications
6
169
1
Order By: Relevance
“…In addition, T286 phosphorylation has been shown to decrease the dissociation rate of the kinase from the PSD (Shen et al, 2000;Bayer et al, 2006;Yoshimura and Yamauchi, 1997;Dosemeci et al, 2002). It has also been observed that autophosphorylation of T305/6 inhibits binding of αCaMKII to the PSD and several PSD proteins (Strack et al, 1997b;Leonard et al, 2002;Robison et al, 2005). Furthermore, it has been demonstrated that T305/6 phosphorylation increases the dissociation rate of the kinase from the PSD (Shen et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In addition, T286 phosphorylation has been shown to decrease the dissociation rate of the kinase from the PSD (Shen et al, 2000;Bayer et al, 2006;Yoshimura and Yamauchi, 1997;Dosemeci et al, 2002). It has also been observed that autophosphorylation of T305/6 inhibits binding of αCaMKII to the PSD and several PSD proteins (Strack et al, 1997b;Leonard et al, 2002;Robison et al, 2005). Furthermore, it has been demonstrated that T305/6 phosphorylation increases the dissociation rate of the kinase from the PSD (Shen et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have indicated that αCaMKII autophosphorylation of T286 enhances binding of the kinase to the PSD and several of its constituents (Bayer et al, 2001;Strack et al, 1997b;Strack and Colbran, 1998;Gardoni et al, 1999;Leonard et al, 2002;Strack et al, 2000). In addition, T286 phosphorylation has been shown to decrease the dissociation rate of the kinase from the PSD (Shen et al, 2000;Bayer et al, 2006;Yoshimura and Yamauchi, 1997;Dosemeci et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This inter-subunit phosphorylation of Thr-286/287 converts the kinase into a high affinity binding protein for Ca 2ϩ /CaM, and the kinase becomes an activatorindependent autonomous enzyme (3). The autophosphorylation also leads to increased affinity of the kinase for several proteins near the sites of elevated Ca 2ϩ with functional consequences (4,5).…”
mentioning
confidence: 99%